POLA KEMITRAAN CONTRACT FARMING ANTARA PETANI CLUSTER DAN PT MITRATANI AGRO UNGGUL (PT MAU) DI KABUPATEN LAMPUNG SELATAN - Azhari Maliki; R Hanung Ismono; Helvi Yanfika (Lampung University, 2013)
This research aimed to know the partnership pattern of contract farming between cluster farmers and PT Mitratani Agro Unggul and the partnership benefits for the farmers. This research was conducted in South Lampung Regency in October 2012, in which 12 farmers joined this partnership program as respondents. The data was analyzed by descriptive and farming income analysis. The results showed that the related partners to contract farming partnership covered: capital assistance, marketing, and knowledge transfer support or trainings. The contract farming was an official partnership containing the rules in the written contracts of agreement. The partnership of contract farming had not economically given benefit to the cluster of pepper farmers, because of the low of farmers’ productivities. These low productivities were caused by several problems, such as climate, cultivation technic, bug’s infections, and also lending taradinnes. The highest R/C was 1.25 and the lowest R/C was 1.01. Farmers also got non-economically benefits; one of those was the existence of legal law microfinance institution and improvement of the derivative products of chili pepper. Keywords: cluster, chili pepper, contract farming, partnership